AdaptiveRME e aspectCompose: um middleware adaptativo e um processo de composição orientado a aspecto para o desenvolvimento de software móvel e ubíquo - Rocha, Lincoln Souza (2007)
Ubiquitous computing is an extensive computational paradigm, which can provide solutions to regular citizens or can be useful to handle complex medical environment data, for example. This paradigm proposes a new human-computer interaction approach based on the proactivity of computers that makes users’ life easier. However, this approach demands a high level of collaboration and communication among the computational elements that compose the mobile and ubiquitous environments. One of the main challenges is related to the way of conceiving software systems capable of dealing with the high variation of resources and services, along with guaranteeing the interoperability among the diversity of computational elements that compose these environments. Therefore, this work proposes an adaptive middleware for móbile and ubiquitous environments that intends to solve heterogeneity and dynamicity problems. This dissertation also proposes a software composition process to reduce coupling between the proposed middleware and applications. The middleware uses dynamic adaptation and support for context-aware software development mechanisms, and the composition process uses Aspect-Oriented Programming (AOP) techniques. A case study is developed to evaluate the adaptive middleware’s functionalities and demonstrate the composing process. Furthermore, a performance analysis is presented to measure the proposed middleware’s impact in a wireless network.